The Evaluation of Fresh Cheese with Basil Addition - Adriana Pavelková; Alena Janigová; Jana Tkáčová (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of the study was to assess the chemical and sensory characteristics of fresh cheese with the addition of basil. The basil was added in the form of hydrosol (H1 - 1.0 mL; H2 - 1.25 mL; H3 - 1.50 mL; H4 - 1.75 ml to 1 L of milk). The samples of produced fresh cheeses were evaluated sensory by Time-Intensity method and chemically (fat content, dry matter, titrable acidity) after 24 hours and vacuum-packed samples of cheeses were evaluated after 7 days storage under refrigeration. From the obtained chemical results we can state that in the case using of hydrosol was increased dry matter after 7 days of storage, the average 4.25 %. Content of acid substances was also increased, from 22.5 °SH to 30.5 °SH. Content of fat was ranged from 3.5 g.100 g-1 (H2) to 6.0 g.100 g-1 (H1) after 24 hours and from 6.0 g.100 g-1 (H4) to 7.3 g.100 g-1 (H3) after 7 days in samples with the addition of hydrosol.  From the obtained sensory results we can conclude that from samples of fresh cheese with the addition of basil hydrosol were best evaluated samples H3 (the addition of 1.5 mL hydrosol to 1 L of milk) after 24 hours and 7 days of storage and the weakest intensity was observed in sample H4 (the addition 1.75 mL to 1 L of milk). We can state, that using basil in form as hydrosol can be good alternative for increasing consumption of fresh cheese.